New Dimensions for Library Services in Ghana - Ammisah-Arthur, Matilda (Ghana Library Journal, 1997)
In recent years the priority that was given to libraries has been substantially reduced in the face of competing social needs, increasing economic and changing government fiscal policies. Despite these, libraries are expected to be cost-effective in order to ensure the maximization of the use of their resources. Faced with the declining levels of financial support and the rising demand for accountability, libraries are under pressure to re-examine their operations and priorities.